Leadership Style, Work Motivation and Organizational Culture - Mohammad Yahya Arief (Publisher Cv. Inara, 2021)
The purpose of this study was to determine and analyze the influence of leadership style, work motivation and organizational culture on PG Employee Performance. Asembagus. The research method used is exploratory research, where variables are measured by a Likert scale. The data collection method was carried out by interview (interview), with a questionnaire and documentary study. The population in this study were all PG employees. Asembagus as many as 215 people. Withdrawal of the number of samples with the Slovin formula 68 people. Data processing using SPSS software, with descriptive analysis and hypothesis testing multiple linear regression analysis. The results showed that: (1) partially the leadership style variable affects the performance of PG employees. Asembagus (2) partially work motivation variables affect employee performance at PG. Asembagus; (3) partially organizational culture variables affect employee performance at PG. Asembagus; (4) Simultaneously there is a positive and significant influence between the variables of leadership style, work motivation and organizational culture on employee performance at PG. Asembagus.